Law, drugs and the politics of childhood : from protection to punishment - Flacks, Simon (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book examines how and why drug laws persist in the way that they do, and why particular populations benefit, or suffer, more than others. This biopolitical reading of drug control also provides a more theoretically coherent explanation for the centrality of race to disproportionate regimes of policing and imprisonment. The work provides an abridged history of the association between drug control, childhood and race, considering this relationship from a biopolitical perspective. It problematises some of the reforms that have taken place in recent years, notably in respect of cannabis depenalisation in countries such as Canada an.d the US, suggesting that such measures continue to serve as securitization practices through which law and order responses to substance use remain paramount. In doing so, it asks whether reform initiatives justified on the basis of child protection rationalities are in fact such a significant break from the past. It considers whether depenalisation is either as unambiguously good, or definitely bad, as many observers would have it, but rather manifests the political choices and tensions lying at the heart of contemporary drug debates. Using analysis of sentencing measures for drugs offenders, the discussion then considers the ways in which rationalities of child protection serve to justify the incarceration of users and suppliers. The book subsequently turn to the question of parents, and particularly the ways in which drug-using mothers may be sterilised, incarcerated and otherwise stigmatised as a result of law and policy measures. The final chapters consider child drug users as agents, exploring the ways in which some children experience exclusion and discrimination as a result of school drug policies and criminal justice practices. Existing regimes of drug control that rely on imaginaries of childhood, it is argued, merely serve to cause harm to under-18s who use or supply substances"--
Drugs and childhood : a genealogy -- Drug law reform and the politics of childhood -- Endangering childhood : framing the drug pusher -- Family justice and child protection : mums on drugs -- Punishing children : problematising school exclusions.
OCLC-licensed vendor bibliographic record.
Keywords: Drugs -- Law and legislation; Drugs -- Law and legislation -- Criminal provisions; Drug abuse -- Law and legislation; Children -- Legal status, laws, etc; Children -- Drug use; Children -- Drug use -- Prevention; Children of drug addicts; Narcotic laws; LAW / General; LAW / Civil Rights; LAW / Criminal Law / General